Expert evidence on coercive control in support of self-defence: the trial of Teresa Craig - Sheehy, Elizabeth A. (Criminology & criminal justice, 2018)
This article uses the transcripts from an abused woman’s trial in Canada for first-degree murder of her husband to explore the expert testimony provided by Dr Evan Stark to support a potential defence of self-defence. His evidence focused on coercive control theory and provoked extreme resistance from Crown prosecutors, such that self-defence was ultimately removed from the jury’s consideration. The trial illustrates the advantages and challenges of using coercive control theory as well as its future potential.